2017
DOI: 10.1111/cge.13032
|View full text |Cite
|
Sign up to set email alerts
|

A recognizable systemic connective tissue disorder with polyvalvular heart dystrophy and dysmorphism associated with TAB2 mutations

Abstract: Deletions encompassing TAK1-binding protein 2 (TAB2) associated with isolated and syndromic congenital heart defects. Rare missense variants are found in patients with a similar phenotype as well as in a single individual with frontometaphyseal dysplasia. We describe a family and an additional sporadic patient with polyvalvular heart disease, generalized joint hypermobility and related musculoskeletal complications, soft, velvety and hyperextensible skin, short limbs, hearing impairment, and facial dysmorphism… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
55
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(60 citation statements)
references
References 23 publications
5
55
0
Order By: Relevance
“…The proband also displays more cardiac issues overall than his sister, who did not have valve regurgitation or myxoid degeneration of valves. Both siblings were notable for hypermobility, which has been well recognized in previous literature (Cheng et al., ; Ritelli et al., ). Both exhibited mild myopia, which has been recorded in one individual who coincidentally also has a pathogenic nonsense variant in TAB2 , although this may well be multifactorial (Ritelli et al., ).…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…The proband also displays more cardiac issues overall than his sister, who did not have valve regurgitation or myxoid degeneration of valves. Both siblings were notable for hypermobility, which has been well recognized in previous literature (Cheng et al., ; Ritelli et al., ). Both exhibited mild myopia, which has been recorded in one individual who coincidentally also has a pathogenic nonsense variant in TAB2 , although this may well be multifactorial (Ritelli et al., ).…”
Section: Discussionsupporting
confidence: 65%
“…Both siblings were notable for hypermobility, which has been well recognized in previous literature (Cheng et al., ; Ritelli et al., ). Both exhibited mild myopia, which has been recorded in one individual who coincidentally also has a pathogenic nonsense variant in TAB2 , although this may well be multifactorial (Ritelli et al., ). The sloping shoulders seen in the sister and high‐arched palate seen in the proband seem to be unique features.…”
Section: Discussionsupporting
confidence: 65%
“…Here, we report the molecular proof of the pathogenic considerations, which emerged by the previous description of a novel disorder resembling the 6q25.1 microdeletion syndrome and additional connective tissue features (Ritelli et al, ). In our previous work, we emphasized the pleiotropic nature of the disorder due to the heterozygous TAB2 c.1398dup variant.…”
Section: Discussionmentioning
confidence: 55%
“…This study focused on the TAB2 (RefSeq NM_015093) variant found in Family 1 in our previous work (Ritelli et al, ). The variant has been submitted to Leiden Open Variation Database (https://databases.lovd.nl/shared/phenotypes/0000175660, patient ID 00235348).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation